17-Hydroxyprogesterone caproate for the prevention of recurrent preterm birth: a systematic review and meta-analysis taking into account the PROLONG trial = 17-Hydroxyprogesteroncaproat zur Prävention der wiederholten Frühgeburt : systematische Übersicht und Metaanalyse unter Berücksichtigung des PROLONG-Trials - Kuon, Ruben-Jeremias; Berger, Richard; Rath, Werner (Geburtshilfe und Frauenheilkunde, 2021)
Prior spontaneous preterm birth is a strong risk factor for the recurrence of spontaneous preterm birth in a subsequent pregnancy and has been evaluated in prevention studies using progesterone (natural progesterone administered orally or vaginally, and 17-hydroxyprogesterone caproate [17-OHPC]) as a selection criterion. Based on the findings of a randomized, placebo-controlled study, 17-OHPC was approved for use in 2011 by the Food and Drug Administration in the USA for the prevention of recurrent preterm birth. The approval was granted with qualification that a subsequent confirmatory study would need to be carried out, the results of which have just been published (PROLONG trial). A systematic literature search for the period from 1970 to April 2020 using the search terms “preterm birth” and “17-OHPC” or “progesterone” was carried out. Only randomized, placebo-controlled studies of women with singleton pregnancies who received 17-OHPC to prevent recurrent preterm birth were included in the subsequent meta-analysis. The relative risk and associated 95% confidence intervals were calculated. The heterogeneity between studies was evaluated with statistics. In addition to the original study used for the approval and the PROLONG trial, only one other study was found which met the inclusion criteria (total number of patients: 2221). With considerable heterogeneity between the studies, particularly with respect to the risk factors for preterm birth, the comparison between 17-OHPC and placebo showed no significant reduction in preterm birth rates before 37, 35 and 32 weeks of gestation and no significant differences with regard to the prevalence of miscarriage before 20 weeks of gestation or fetal deaths (antepartum or intrapartum) after 20 weeks of gestation and neonatal morbidity. Based on the currently available data, 17-OHPC cannot be recommended for the prevention of recurrent preterm birth. Further randomized, placebo-controlled studies with clearly defined, comparable risk factors are required to identify the group of pregnant women which could benefit from the use of 17-OHPC to prevent preterm birth